Fund performance during recessions and expansions in Korea - Mun-Kyung Cheong; Yong-Hyeon Kim; Jellna Chung (Global Business & Finance Review (GBFR), 2020)
Purpose: This study explores the relationship between the performances of national equity funds and business cycles in Korea. Design/methodology/approach: First, this research examines how fund performance is better in recessions than in expansion periods and then analyzes fund performance by dividing funds into active and passive operating styles. Last, what risk factors affect performance with respect to business cycles and operating cycles are investigated. Findings: The empirical findings show that fund performance is affected by the economic variables of short-term interest rates, credit risk spread, growth in money stock, and corporate value.However, the effects change with the business cycle.In addition, the fund performance of overall, internal, and outsourcing investments is better in recessions than in expansion periods, which agrees with foreign studies. Research limitations/implications: When assessing fund managers abilities, not only quantitative performance but also qualitative assessment - economic conditions - become important.It is necessary to evaluate fund performance with a system that considers economic fluctuations. Originality/value: This is the first research to analyze the performance of the national pension fund using the regime-switching model in the Korean market.
Keywords: 650; Pension funds; Fund operating styles; Economic fluctuations; Regime-switching model